A Changing Game: Ethnicity, Gender, and Nation in the US American Soccer Film. (December 2014) - Haas, Astrid
<x content-type="archive" xml:space="preserve">Abstract</x> Both sport and film play a key role in contemporary US American popular culture. They are widely regarded as legitimate carriers and formative instances of social identities such as ethnicity, gender, or nationality, and they have capitalized upon one another with increasing success. Soccer and soccer films provide a case in point, as both the sport and its treatment in US American feature films are currently undergoing a change from a rather marginal position to a somewhat secure place within the cultural mainstream. This essay analyses five recent American soccer films with a particular focus on how they frame soccer as an ethnic, gendered, and 'national' game in a US context.